Looking beyond oral mucosa: Initial results of everted saphenous vein graft urethroplasty (eSVGU) in long anterior urethral strictures - Arif Akhtar (Taylor & Francis Group, 2017)
Objective: To prospectively evaluate the feasibility and initial results of an everted saphenous vein graft (eSVG) as a dorsolateral onlay, in patients with long anterior urethral strictures and/or chronic tobacco users. Patients and methods: In all, 20 patients with long anterior urethral strictures (>7 cm) and/or chronic tobacco exposed oral mucosa were included in the study. The harvested SVG was hydro-distended, detubularised, and everted. Substitution urethroplasty using an eSVG was performed using a dorsolateral onlay technique. Symptoms were assessed using the International Prostate Symptom Score (IPSS) and uroflowmetry at 1, 3 and 6 months; and voiding and retrograde urethrograms, and urethroscopy were done at 3 months. Failure was defined as failure to void, need for interventions in form of direct-vision internal urethrotomy or endodilatation. Results: Three patients were excluded because they underwent a staged urethroplasty. In all, 17 patients underwent eSVG substitution urethroplasty. The mean (SD, range) follow-up of our patients was 17.64 (5.23, 10–26) months. The mean (SD, range) length of the strictured segment was 14 (2.5, 10–18) cm and the length of the harvested SVG was 16.3 (2.7, 12–20) cm. The mean (SD) IPSS at 1, 3 and 6 months after catheter removal was 10 (2.8), 10 (3.4) and 10 (1.4) and the quality-of-life score was 1.76 (0.5), 2.05 (1.0) and 2.05 (1.0), respectively. Postoperatively, endodilatation was required in two patients. Complete failure occurred in one patient. Conclusions: An eSVG, as a dorsolateral onlay graft, is a promising and prudent option for long anterior urethral strictures, especially in patients with poor oral hygiene and chronic tobacco use.